Systemic Inflammation in Pregnant Women With Latent Tuberculosis Infection - Naik, Shilpa; Alexander, Mallika; Kumar, Pavan; Kulkarni, Vandana; Deshpande, Prasad; Yadana, Su; Leu, Cheng-Shiun; Araújo-Pereira, Mariana; Andrade, Bruno B.; Bhosale, Ramesh; Babu, Subash; Gupta, Amita; et al. (Frontiers in Immunology, 2021)
Background: Recent studies in adults have characterized differences in systemic inflammation between adults with and without latent tuberculosis infection (LTBI+ vs. LTBI-). Potential differences in systemic inflammation by LTBI status has not been assess in pregnant women. Methods: We conducted a cohort study of 155 LTBI+ and 65 LTBI- pregnant women, stratified by HIV status, attending an antenatal clinic in Pune, India. LTBI status was assessed by interferon gamma release assay. Plasma was used to measure systemic inflammation markers using immunoassays: IFNβ, CRP, AGP, I-FABP, IFNγ, IL-1β, soluble CD14 (sCD14), sCD163, TNF, IL-6, IL-17a and IL-13. Linear regression models were fit to test the association of LTBI status with each inflammation marker. We also conducted an exploratory analysis using logistic regression to test the association of inflammatory markers with TB progression. Results: Study population was a median age of 23 (Interquartile range: 21-27), 28% undernourished (mid-upper arm circumference (MUAC) <23 cm), 12% were vegetarian, 10% with gestational diabetes and 32% with HIV. In multivariable models, LTBI+ women had significantly lower levels of third trimester AGP, IL1β, sCD163, IL-6 and IL-17a. Interestingly, in exploratory analysis, LTBI+ TB progressors had significantly higher levels of IL1β, IL-6 and IL-13 in multivariable models compared to LTBI+ non-progressors. Conclusions: Our data shows a distinct systemic immune profile in LTBI+ pregnant women compared to LTBI- women. Data from our exploratory analysis suggest that LTBI+ TB progressors do not have this immune profile, suggesting negative association of this profile with TB progression. If other studies confirm these differences by LTBI status and show a causal relationship with TB progression, this immune profile could identify subsets of LTBI+ pregnant women at high risk for TB progression and who can be targeted for preventative therapy.